FUNGSI PAGUYUBAN KAMPUNG BATIK DALAM PELESTARIAN BATIK SEMARANG DI KOTA SEMARANG - Pertiwi, Michelia Nindya (Solidarity: Journal of Education, Society and Culture, 2014)
This research aims to discuss about the function of the community of Kampung Batik to preserving batik Semarang also identify driving and inhibiting factors in the preservation batik Semarang. The method in this research is a qualitative method using a descriptive approach. Location of research in Kampung Batik Semarang. Data collection techniques of research using observation, interviews, and documentation. The validity of the research data obtained by triangulation and member checks held. Analysis of the data in this study using the technique of data collection, data reduction, data display, and conclusion or verification. Function of community of Kampung Batik to preserving Semarang batik, done by : 1) function of economic,function of social culture, and function of preserving Â Activities of community of Kampung Batik to preserving civilization Semarang batik, done by : 1) promotion and exhibition of batik Semarang in various places; 2) held a batik training provided to entire community of various generations; 3) organize the development of innovation towards motifs and patterns of batik Semarang by taking icon of Semarang , and innovate the batik technique in a way mencolet staining techniques. The driving factor for the implementation of conservation programs Batik Semarang : 1) UNESCOs decision in 2008 that decided batik as an Indonesian cultural non-material origin and local regulations No.14 2011 Semarang which makes batik Semarang as cultural identity; 2) provision of fund and batik equipment and fund loan assistance; 3) focusing conservation of batik Semarang which was centered in Kampung Batik. Inhibiting factor for the implementation of batik Semarang conservation program : 1) social problem in the community; 2) conservation programs stopped; 3) focusing conservation of batik Semarang in Kampung Batik only in RW 1 and RW 2 area. Kampung Batik conditions are not met the criteria to be used as industrial centers of batik. Â